Circulating epithelial cells in patients with thyroid carcinoma - Winkens, T.; Pachmann, K.; Freesmeyer, M. (Nuklearmedizin - NuclearMedicine, 2013)
Goal: To investigate whether circulating epithelial cells (CEC) recognized via the epithelial cell adhesion molecule (EpCAM) can be identified in the blood of patients with thyroid carcinoma, given that CEC have already been detected in other types of carcinoma and are considered a potential marker of tumour dissemination. Patients, methods: Blood samples of patients with active differentiated thyroid carcinoma (DTC) (n = 50) were compared to samples of patients with: a) recent surgical excision of a thyroid carcinoma (postOP-DTC) (n = 16); b) athyreotic, tumour-free status after radioiodine ablation (AT-DTC) (n= 33); and c) benign thyroid diseases (BTD) (n = 51). Samples of volunteers with normal thyroid parameters (NT) (n = 12) were also investigated. Cells from EDTAblood were subjected to erythrocyte lysis, isolated by centrifugation, and incubated with a fluorescence-labeled antibody against EpCAM. The numbers of vital cells were counted via fluorescence microscopy. Results: CEC were identified in all groups, with the postOP-DTC group showing the highest mean CEC numbers of all groups. The DTC group had significantly higher CEC numbers than the NT group, and numerically higher numbers than the other groups, although not reaching statistical significance. Within the DTC group there was a correlation between levels of serum thyroglobulin and numbers of CEC (r = 0.409, p = 0.003). Conclusions: High CEC numbers were not specific to thyroid carcinoma. The methodology used here, based on a single measurement does not allow to identify severe forms of DTC, emphasizing the need of longitudinal measurements throughout therapy. Detection and characterization of tumour thyroid cells in circulation should be based on additiona l consideration of tissue-specific characteristics.
Keywords: Differentiated thyroid carcinoma; circulating epithelial cells; EpCAM; CEC